A LC-MS/MS Approach for the Identification of Degradation Products of Serdexmethylphenidate and Dexmethylphenidate and Elucidation of their Degradation Pathway - Gollu, Gowri; Gummadi, Sowjanya; Sahoo, Santosh Kumar; Panda, Jagadeesh (Current Spectroscopy and Chromatography, 2025)
IntroductionA combination of serdexmethylphenidate and dexmethylphenidate are used to treat attention deficiency hyperactivity disorder. A stability-indicating RP-HPLC method has been developed and reported in the literature. As there is no study on the degradation product identification, in this work, the degradation behavior of serdexmethylphenidate and dexmethylphenidate was explored by subjecting combined dosage to the forced degradation study by applying the developed RP-HPLC method. Further, plausible structures and fragmentation patterns of all the degradation products were identified by the LC-MS/MS study.MethodsThe forced degradation study was conducted by exposing the combined dosage form (Azstarys) as per International Council of Harmonization (ICH) guideline Q1A (R2). Using LC-MS/MS, MS spectra were obtained. Based on the m/z values and molecular formula, probable structures of degradation products were elucidated.Results and DiscussionA total of 7 degradation products were detected, of which, 4 degradation products were formed from serdexmethylphenidate. The remaining 3 degradation products were formed from dexmethylphenidate. The possible structures and fragmentation patterns of all the degradation products were examined with the help of the LC-MS/MS study.ConclusionAs possible structures and fragmentation patterns were identified by the LC-MS/MS study, this method may help in the development of quality dosage forms, maintaining proper storage conditions, and also in impurity profiling studies.
Keywords: RP-HPLC method